Annual Plan West Bengal 1994-95 Volume 1 - Planning Commission (Planning Commission, 1994)
The Annual Plan (1994-95) of the State is being formulated at a time when the Indian Economy has entered into an economic crisis with implications extending beyond the usual economic sphere. For the first lime since Independence, our country, as the data published in the latest Economic Survey (1992-93) of the Government of India show, has entered into the debt-trap of external loans in the specific sense that more than 100% of the external loans taken during the first nine months of 1992-93 have been used for repayment of past loans. It is at this time that assaults are being made on the sovereignty of the country, and the marks of submission before the conditionalities of IMF loan are glaringly visible in several spheres.
Development and Planning Department, Government of West Bengal